Continuous artificial light potentially disrupts central and peripheral reproductive clocks leading to altered uterine physiology and reduced pregnancy success in albino mice - Das, Megha; Minocha, Tarun; Kumar, Dhanananajay; Yadav, Sanjeev Kumar; Haldar, Chandana (Springer Nature, 2022)
Aims: The mechanism behind clock coordination in female reproductive disorders is poorly understood despite the known importance of coordinated and synchronized timing of central and clocks in reproductive organs. We investigated the effect of continuous artificial light (LL) on the central and peripheral reproductive clock gene (Bmal1, Clock, Per1, Per2 and Cry1) and its downstream regulators (Hgf, PR-A and HOXA10) during non-pregnancy and pregnancy phases of female mice. Main methods: Mice (n = 60) in two sets, were maintained under continuous light (LL) and natural day cycle (LD;12L: 12D) for both non-pregnant and pregnant study. Tissues from hypothalamus-containing SCN, ovary, uterus and serum were collected at different zeitgeber time points (ZT; at 4-h intervals across 24-h periods). Key findings: LL exposure desynchronized the expressions of the clock mRNAs (Bmal1, Clock, Per1, Per2 and Cry1) in SCN, ovary, and uterus along with Hgf mRNA rhythm. LL significantly increased the thickness of endometrial tissues. Furthermore, the pregnant study revealed lower serum progesterone level during peri- and post-implantation under LL along with downregulated expression of progesterone receptor (PR) as well as progesterone dependent uterine Homeobox A-10 (Hoxa10) proteins with lowered pregnancy outcomes. Significance: Our result suggests that LL disrupted the circadian coordination between central and clock genes in reproductive tissue leading to interrupted uterine physiology and altered pregnancy in mice. This led us to propose that duration of light exposure at work-places or home for females is very important in prevention of pregnancy anomalies.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Chronodisruption; Clock genes; Decidualization; Estradiol; Hepatocyte growth factor; Animals; ARNTL Transcription Factors; Circadian Rhythm; Female; Hypothalamus; Mice; Photoperiod; Progesterone; RNA, Messenger; Clocks; Genes; Histology; Mammals; Tissue; messenger RNA; progesterone; transcription factor ARNTL; Artificial light; Chronodisruption; Clock genes; Decidualization; Estradiol; Hepatocyte growth factor; Progesteron; Progesterone receptor; Reproductive disorders; Reproductive organs; animal; circadian rhythm; female; genetics; hypothalamus; metabolism; mouse; photoperiodicity; physiology; Obstetrics